A consistent multi-resolution particle method for fluid-driven granular dynamics - Jandaghian, Mojtaba; Shakibaeinia, Ahmad (Advances in Water Resources, 2023)
Keywords: Ahmad_Shakibaeinia

Field monitoring of river ice processes in the vicinity of ice control structures in the province of Quebec, Canada - Pourshahbaz, Hanif; Ghobrial, Tadros; Shakibaeinia, Ahmad (Canadian Journal of Civil Engineering, 2023)
Over the past decades, a variety of ice control structures (ICSs) have been designed and built, but to date, there has been no systematic evaluation of the effectiveness of these structures. To achieve this objective, first an understanding of the interaction between different ice processes and the ICSs must be established. For this purpose, a total of four ICSs located in the province of Québec were monitored during the 2021–2022 winter. The results showed that the ice jam holding time could vary from 1.5 to 68.5 h. The release of the jam was mechanically driven when the ratio of release to initiation Froude number was higher than one and was thermally driven when this ratio was lower than one, and the water temperature increased between initiation and release. Also, as the ratio of the total pier spacing to upstream river width increased, the holding time decreased.
Keywords: Ahmad_Shakibaeinia; Infolettre; Infolettre_Octobre_2023

Three-dimensional fully-Lagrangian DEM-SPH modeling of river ice interaction with control structures - Billy, Clement; Shakibaeinia, Ahmad; Ghobrial, Tadros (Cold Regions Science and Technology, 2023)
Ice control structures (ICSs) play a vital role in preventing ice jams and safeguarding communities by either stabilizing ice cover or relocating jams upstream. Understanding and modeling the interaction between ice floes and these structures is crucial for assessing their effectiveness and optimizing their designs. However, simulating these complex multi-physics systems poses challenges for numerical techniques. In this paper, we introduce and evaluate a fully-Lagrangian mesh-free continuum-discrete model based on the Smoothed Particles Hydrodynamics (SPH) method and Discrete Element Method (DEM) for three-dimensional (3D) simulation of ice interactions with control structures. To validate and parameterize the numerical model, we conduct two sets of experiments using real and artificial ice materials: (1) dam-break wave-ice-structure interaction and (2) ice-ICS interaction in an open channel. By comparing numerical and experimental results we demonstrate the capability and relative accuracy of our model. Our findings indicate that real ice generally exhibits faster jam evolution and ice passage through the ICS compared to artificial ice. Moreover, we identify the Froude number and ice material type as important factors influencing jam formation, evolution, and ICS effectiveness. Through sensitivity analysis of material properties, we highlight the significant impact of friction and restitution coefficients.
Keywords: Ahmad_Shakibaeinia; Infolettre; Infolettre_Septembre_2023